Access to Clinical Trials for Adolescents and Young Adults With Cancer: A Meta-Research Analysis. Issue 4 (1st August 2019) - de Rojas, Teresa; Neven, Anouk; Terada, Mitsumi; García-Abós, Miriam; Moreno, Lucas; Gaspar, Nathalie; Péron, Julien
Abstract: Background: The 18-year-old age limit for inclusion in clinical trials constitutes a hurdle for adolescents and young adults (AYAs) with cancer. We analyzed the impact of this age barrier on the access of AYAs to cancer trials and novel therapies. Methods: ClinicalTrials.gov was searched to identify all the trials including patients with 10 malignancies relevant for AYAs (January 2007 to July 2018). The trials were categorized as pediatric (patients <18 y), adult (≥18 y), and transitional (including adult and pediatric patients). Transitional trials with a lower limit between 12 and 18 years and an upper limit younger than 40 years were considered AYA-specific. Results: Of 2764 identified trials, 2176 were included: 79% adult, 19% transitional, 2% pediatric. Five trials were AYA-specific. The proportion of academic trials was higher for transitional (69%; 288 of 421) than for adult trials (48%; 832 of 1718) ( P < .0001). The total number of new trials increased over the years (156 in 2007; 228 in 2017); however, the number of transitional trials remained stable. The availability of trials increased with age, with a major increase at age 18 years: at age 17 years, 20% (442 of 2176) of trials were potentially accessible vs 95% (2075 of 2176) at 18 years. For trials investigating targeted therapies, this increase was 460% (197 trials available at age 17 years; 901 at 18 years) and for immunotherapies, 1200% (55 at age 17 years; 658 at 18 years). Conclusions: AYAs have limited access to cancer trials and innovative therapies, with no improvement over the last decade. The 18-years-old age limit continues to be a major hurdle. Our findings are consistent with the internationally supported idea that age inclusion criteria in oncological trials should be changed.